Modelling of chewing and aroma release during oral processing : model development, model validation and comprehensive examples for food design : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemical and Bioprocess Engineering, Massey University, Palmerston North, New Zealand - Mohd Firdaus How, Muhammad Syahmeer How (Massey University, 2021)
Chewing is complex because of its sub-processes and interactions, and inter-individual differences between people. The development of mechanistic models can be a tool to explore these aspects and can lead to the development of foods with controlled digestion outcomes and improved sensory appeal. A mechanistic chewing model was developed based on selection and breakage processes and implemented using a discretised population balance to predict the changes in bolus particle size distribution during chewing. The model was successfully implemented on peanuts, which gave confidence for its implementation to cooked white rice, which is an aromatic food system and has strong correlations with in vitro digestion. The relationship between panellists physiological, chewing and aroma release parameters during mastication of white rice were investigated in vivo to provide insights for model development. The findings showed that the dynamic behaviour of aroma release of all five subjects followed a similar trend with the breakdown pathways where subjects with smaller particles size in their bolus had higher aroma release. The study paved the first step in understanding the role of chewing on aroma release of cooked white rice and provided a range of oral processing behaviours for model validation. A coupled chewing and aroma release model was developed and validated against experimental data. Adjusting the input parameters from the coupled model showed that the portion size, initial concentration of the studied aroma compound, initial liquid volume and the rice pasted fraction were the most sensitive product-related parameters. The oral cavity volume, pharynx volume, nasal cavity volume and the breathing frequency were the most sensitive physiological parameters. The physico-chemical parameter which had the most significant effect was the mass transfer coefficient in the saliva phase. Examples were also given to show the difference in aroma release when aroma compounds of varying partition coefficients were used. The work from this thesis constitutes the first step in the application of mechanistic chewing models as a tool for food design. The next step will be to expand these models to a wider range of food systems and to a larger number of individuals to improve the model reliability.
These Figures were removed for copyright reasons: 2-1 (=Lucas et al., 2002 Fig 1), 2-2 (=Hiiemae, 2004 Fig 1), 2-4 (=Mosca & Chen, 2017 Graphical abstract), 2-6 (=Zhang et al., 2019, Fig 1) and 2-11 (=Doyenette et al., 2014 Fig 1).
Keywords: Mastication; Food; Odor; Mathematical models; 400407 Process control and simulation